2020
DOI: 10.1038/s41438-020-00413-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and molecular interplay between two viruses and powdery and downy mildews in two grapevine cultivars

Abstract: Grapevine may be affected simultaneously by several pathogens whose complex interplay is largely unknown. We studied the effects of infection by two grapevine viruses on powdery mildew and downy mildew development and the molecular modifications induced in grapevines by their multiple interactions. Grapevine fanleaf virus (GFLV) and grapevine rupestris stem pitting-associated virus (GRSPaV) were transmitted by in vitro-grafting to Vitis vinifera cv Nebbiolo and Chardonnay virus-free plantlets regenerated by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
4
14
0
Order By: Relevance
“…This highly interesting observation was somehow confirmed in a very elegant experiment, where authors transmitted GFLaV and grapevine rupestris stem pitting-associated virus (GRSPaV), by in vitro -grafting, to Nebbiolo and Chardonnay. Upon subsequent downy and powdery mildew infection, GFLV-infected plants showed a reduction in severity of the diseases caused by powdery and downy mildews in comparison to virus-free plants, which highlights a potential upregulation of plant innate immunity by GLRD infection ( Gilardi et al, 2020 ).…”
Section: Virus Infectionsmentioning
confidence: 99%
“…This highly interesting observation was somehow confirmed in a very elegant experiment, where authors transmitted GFLaV and grapevine rupestris stem pitting-associated virus (GRSPaV), by in vitro -grafting, to Nebbiolo and Chardonnay. Upon subsequent downy and powdery mildew infection, GFLV-infected plants showed a reduction in severity of the diseases caused by powdery and downy mildews in comparison to virus-free plants, which highlights a potential upregulation of plant innate immunity by GLRD infection ( Gilardi et al, 2020 ).…”
Section: Virus Infectionsmentioning
confidence: 99%
“…In our dataset, VvWRKY18 (VIT_04s0008g05760) was strongly expressed in ‘Nebbiolo’ at E-L31, and then its transcriptional rates decreased during ripening, while in ‘Barbera’, the expression levels of this gene were constant at all sampling times ( Figure 3 ). Interestingly, the constitutive high basal expression of VvWRKY18 in ‘Nebbiolo’ was also observed by analyzing the leaves of this cultivar in comparison to ‘Chardonnay’ [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to specific transcription factors, sugars involved in the priming of plant defense responses can modulate defense-related genes [ 59 ]. For instance, the sugar transporter VvSTP13 (VIT_05s0020g03140), which is involved in intracellular glucose uptake, was associated with defense responses in particular rootstock–scion combinations [ 14 ] and in response to fungal infection [ 58 ]. We found that, independently of the year, VvSTP13 was overexpressed in ‘Nebbiolo’ berries at E-L31, while in ‘Barbera’, it was particularly induced at E-L38 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations